1988
DOI: 10.1103/physrevlett.60.2299
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Phenomena Associated with Electron and Proton Transfer in Quinhydrone Charge-Transfer Crystal

Abstract: Studies of the IR vibrational spectroscopy of single crystals of the H-bonded quinhydrone chargetransfer complexes show that a new phase transition occurs upon application of hydrostatic pressure, associated with the proton transfer in the 2D proton lattice. The temperature-and pressure-induced changes in the O-H vibrational spectra are accounted for in terms of the melting of the proton lattice due to the proton tunneling effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(53 citation statements)
references
References 12 publications
(9 reference statements)
3
50
0
Order By: Relevance
“…The few previous studies undertaken on quinhydrone have already demonstrated how phonons drive interesting behavior in this material. Upon applying pressure along its a-axis, Mitani et al found that the behavior of O-H stretching vibration of HQ changes dramatically and posited a cooperative proton-electron tunneling phase of quinhydrone that must be mediated by at least one lattice phonon 16 . Rury et al have also shown that unlike other CT crystals, a Raman-active lattice phonon modulates electron transfer in the charge separated state of quinhydrone 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The few previous studies undertaken on quinhydrone have already demonstrated how phonons drive interesting behavior in this material. Upon applying pressure along its a-axis, Mitani et al found that the behavior of O-H stretching vibration of HQ changes dramatically and posited a cooperative proton-electron tunneling phase of quinhydrone that must be mediated by at least one lattice phonon 16 . Rury et al have also shown that unlike other CT crystals, a Raman-active lattice phonon modulates electron transfer in the charge separated state of quinhydrone 17 .…”
Section: Introductionmentioning
confidence: 99%
“…92). 701 The neutral CT complex of quinhydrone resides at the far right side of the CT region in Fig. 81 since ÁpK a is estimated to be about +17.…”
Section: Multiple Pt and Ct System And Neutral Radicalmentioning
confidence: 99%
“…However, so far no such metallic phase has been obtained under a hydrostatic pressure of up to 2.5 GPa, although the IR and UV-vis spectra indicate melting the hydrogen lattice. 701 A tight binding calculation on a quinhydrone type model complex, which does not include the electron correlation, predicts that the degenerate and metallic state will be achieved under extremely high pressure giving the DA distance of 2.6 Å . 702 …”
Section: Multiple Pt and Ct System And Neutral Radicalmentioning
confidence: 99%
“…The proton‐transfer and electron‐transfer scheme for the BQ‐H2Q couple involves nine independent chemical species. The semiquinone neutral radical HQ ⋅ is generated by one‐electron reduction and one protonation of BQ and/or one‐electron oxidation and one deprotonation of H2Q 3a. In the solid state, the 1:1 charge‐transfer complex (BQ)(H2Q) can be obtained via simultaneous charge‐transfer and hydrogen‐bonding interactions 4.…”
Section: Introductionmentioning
confidence: 99%
“…The electron‐accepting BQ and electron‐donating H2Q molecules form charge‐transfer complexes with neutral electronic ground states, and the degree of charge transfer from H2Q to BQ is estimated to be 0.2 electrons 4. The formation of HQ ⋅ neutral radicals has been reported in high‐pressure environments up to 30 kbar; the magnitude of the change transfer increased, and the high pressure induced proton transfer from H2Q to BQ 3a. Although the detailed physical properties of HQ ⋅ crystal have not yet been well characterized, it is known that the HQ ⋅ neutral radical crystal has degenerate electronic states with electrical conducting and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%